Foot-and-Mouth Disease Virus Lacking the Leader Protein and Containing Two Negative DIVA Markers (FMDV LL3B3D A24) Is Highly Attenuated in Pigs - Michael Eschbaumer; Veronika Dill; Jolene C. Carlson; Jonathan Arzt; Carolina Stenfeldt; Peter W. Krug; John M. Hardham; Jacob E. Stegner; Luis L. Rodriguez; Elizabeth Rieder (Pathogens, 2020)
Inactivated whole-virus vaccines are widely used for the control of foot-and-mouth disease (FMD). Their production requires the growth of large quantities of virulent FMD virus in biocontainment facilities, which is expensive and carries the risk of an inadvertent release of virus. Attenuated recombinant viruses lacking the leader protease coding region have been proposed as a safer alternative for the production of inactivated FMD vaccines (Uddowla et al., 2012, J Virol 86:11675-85). In addition to the leader deletion, the marker vaccine virus FMDV LL3BPVKV3DYR A24 encodes amino acid substitutions in the viral proteins 3B and 3D that allow the differentiation of infected from vaccinated animals and has been previously shown to be effective in cattle and pigs. In the present study, two groups of six pigs each were inoculated with live FMDV LL3BPVKV3DYR A24 virus either intradermally into the heel bulb (IDHB) or by intra-oropharyngeal (IOP) deposition. The animals were observed for 3 or 5 days after inoculation, respectively. Serum, oral and nasal swabs were collected daily and a thorough postmortem examination with tissue collection was performed at the end of the experiment. None of the animals had any signs of disease or virus shedding. Virus was reisolated from only one serum sample (IDHB group, sample taken on day 1) and one piece of heel bulb skin from the inoculation site of another animal (IDHB group, necropsy on day 3), confirming that FMDV LL3BPVKV3DYR A24 is highly attenuated in pigs.